THE EFFECT OF MARKETING MIX AND SERVICES ON CUSTOMER DECISIONS IN USING THE SERVICES OF THE INDONESIAN SHARIA BANK KC KABANJAHE - Widia Anggraini; Muhammad Lathief Ilhamy Nasution; Nur Ahmadi Bi Rahmani (SEAN Institute, 2023)
The marketing mix is ​​a marketing strategy that consists of 4 components, namely: price strategy, product strategy, location strategy, and promotion strategy. This study has 5 independent variables (X), namely: Price, product, promotion and service locations and 1 dependent variable (Y), namely: Customer decision. The research was conducted at Bank Syariah Indonesia KC Kabanjahe by distributing questionnaires to 100 customers which aimed to find out how the marketing mix influences customer decisions in using BSI KC Kabanjahe services and which of the 5 independent variables most influences customer decisions. Quantitative is the research method used with the T test and F test using SPSS for Windows. Based on the research results, the marketing mix has a significant effect on customer decisions and of the 5 independent variables, promotion is the most dominant variable influencing customer decisions.